Multimodal approach in the diagnosis and management of Eales disease: a case report - Adriono, Gitalisa Andayani; Mahfudz, Sausan Rasyid; Triyoga, Ichsan Fauzi (Faculty of Medicine Universitas Indonesia, 2024)
Eales disease is a rare idiopathic occlusive retinal vasculitis with low prevalence in the general population. Its infrequent occurrence limits diagnostic and treatment guidelines, emphasizing the need for ongoing reports to establish effective protocols. This case report describes a patient presenting with symptoms of bilateral retinal vasculitis. Fundus examination revealed vitreous hemorrhage (VH) and peripheral retinal vasculitis. Laboratory and imaging tests were performed to exclude differential diagnoses, leading to Eales disease as the primary diagnosis. Pars plana vitrectomy, panretinal laser photocoagulation, intravitreal anti-vascular endothelial growth factor, and anti-tuberculosis therapy were administered. Long-term follow-up showed satisfactory outcomes. This report suggested Eales disease to be a diagnosis of consideration for ophthalmologists encountering male patients with recurrent VH. Clinical suspicion, including appropriate laboratory testing and imaging, is essential to developing a holistic approach to diagnosis and management, aiming to prevent progression and achieve optimal visual outcomes.